The climate–wildfire–air quality system: interactions and feedbacks across spatial and temporal scales. (28th August 2014) - Stavros, E. Natasha; McKenzie, Donald; Larkin, Narasimhan
Abstract : Future climate change and its effects on social and ecological systems present challenges for preserving valued ecosystem services, including local and regional air quality. Wildfire is a major source of air‐quality impact in some locations, and a substantial contributor to pollutants of concern, including nitrogen oxides and particulate matter, which are regulated to protect public and environmental health. Since climate change is expected to increase total area burned by wildfire and wildfires affect air quality, which is regulated, there is a need to define and study climate, wildfire, and air quality as one system. We review interactions and feedbacks acting across space and time within the climate–wildfire–air quality system, providing a foundation for integrated modeling and for assessing the ecological and social impacts of this system and its broader ecological, social, and scientific implications. WIREs Clim Change 2014, 5:719–733. doi: 10.1002/wcc.303 This article is categorized under: Assessing Impacts of Climate Change > Evaluating Future Impacts of Climate Change Integrated Assessment of Climate Change > Applications of Integrated Assessment to Climate Change